2018
DOI: 10.1038/s41598-018-24428-6
|View full text |Cite
|
Sign up to set email alerts
|

Temporary sequestration of cholesterol and phosphatidylcholine within extracellular domains of ABCA1 during nascent HDL generation

Abstract: The quality and quantity of high-density lipoprotein (HDL) in blood plasma are important for preventing coronary artery disease. ATP-binding cassette protein A1 (ABCA1) and apolipoprotein A-I (apoA-I) play essential roles in nascent HDL formation, but controversy persists regarding the mechanism by which nascent HDL is generated. In the “direct loading model”, apoA-I acquires lipids directly from ABCA1 while it is bound to the transporter. By contrast, in the “indirect model”, apoA-I acquires lipids from the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 42 publications
1
34
0
Order By: Relevance
“…Recently, in baby hamster kidney/ABCA1 cells, Ishigami et al reported that trypsin treatment causes rapid release of PC and cholesterol, suggesting that these lipids are temporarily sequestered at trypsin-sensitive sites on the surface of cells in an ATP-dependent manner. Thus, these sites may be the large extracellular domains (ECDs) of ABCA1, and the lipids may be temporarily sequestered within these ECDs during nascent HDL formation [26]. Although further studies are required to establish the molecular details of the mechanistic links between the ECDs of ABCA1 and the known functions of the transporter, it is clear that ABCA1 function is the first and a crucial step for HDL-C formation.…”
Section: Abca1 and Plasma Lipid Levels 31 Abca1 Reverse Cholesteromentioning
confidence: 99%
“…Recently, in baby hamster kidney/ABCA1 cells, Ishigami et al reported that trypsin treatment causes rapid release of PC and cholesterol, suggesting that these lipids are temporarily sequestered at trypsin-sensitive sites on the surface of cells in an ATP-dependent manner. Thus, these sites may be the large extracellular domains (ECDs) of ABCA1, and the lipids may be temporarily sequestered within these ECDs during nascent HDL formation [26]. Although further studies are required to establish the molecular details of the mechanistic links between the ECDs of ABCA1 and the known functions of the transporter, it is clear that ABCA1 function is the first and a crucial step for HDL-C formation.…”
Section: Abca1 and Plasma Lipid Levels 31 Abca1 Reverse Cholesteromentioning
confidence: 99%
“…To explore this possibility, we performed flow cytometry using the Alexa Fluor 647–labeled D4 domain of perfringolysin O (PFO), which binds to cholesterol in the outer leaflet of the PM 5,18 . FreeStyle293-F suspension cells were used in this assay to obviate the necessity of trypsin treatment, which digests ABCA1 on the cell surface 4 . PFO-D4 binding increased with expression of ABCA1: the median value was about 2-fold higher in the ABCA1-GFP–positive population, but was not much changed in the control GFP–positive cells or ABCA1(MM)-GFP–positive cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ATP-binding cassette A1 (ABCA1) is ubiquitously expressed in the body and plays a key role in the generation of high-density lipoprotein (HDL) 13 . ABCA1 loads cholesterol and phosphatidylcholine (PC) onto a lipid acceptor apolipoprotein A-I (apoA-I) in serum to generate discoidal nascent HDL 4 . Recent work suggested that ABCA1 is associated with other various cellular events, e.g., modulation of growth signaling, adaptation to cell crowding, and inflammatory responses of macrophages 57 .…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence suggest that this involves displacement of cholesterol pools within the PM. Indeed, it has already been shown that ABCA1 actively redistributes cholesterol from lipid-raft nanodomains into smaller pools, and this is crucial for ApoAI binding and generation of HDL molecules [25,26,[51][52][53]. ABCA1 would then create a particular nano-environment at the PM where plasmatic receptors such as ApoAI may bind and be subsequently lipidated with phospholipids and cholesterol.…”
Section: Discussionmentioning
confidence: 99%